2003
DOI: 10.1006/viro.2002.1708
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus-Specific B Cells Induced by Recent Infection in Adults and Children Predominantly Express the Intestinal Homing Receptor α4β7

Abstract: In vivo replication of rotaviruses is generally limited to enterocytes. Because of this restriction, most blood circulating rotavirus-specific B cells are hypothesized to originate in Peyer's patches and should express the intestinal homing receptor alpha4beta7. To test this hypothesis in humans, we used a flow cytometry assay that identifies antigen-activated (IgD-) B cells (CD19+) that express surface rotavirus-specific immunoglobulin. With this assay we could detect rotavirus-specific B cells in both childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 34 publications
5
42
0
4
Order By: Relevance
“…Some of the earlier cells observed here may result from the activation of the IgD + B cell fraction reacting with 2/6-VLP that was detected in NALT and CLN. Such cells present in all the lymphoid tissues analyzed from non-immune mice have already been reported within murine splenic cells [11] and, recently, within human B cells from adults, infants and cord blood, and have been proposed to be responsible for an innate B cell response resulting from the interaction of 2/6-VLP with natural surface anti-VP6 Ab [19,20]. Thus, the high frequency of 2/6-VLP-specific B cells observed here may result from both innate and adaptive B cell responses.…”
Section: Igdmentioning
confidence: 78%
See 1 more Smart Citation
“…Some of the earlier cells observed here may result from the activation of the IgD + B cell fraction reacting with 2/6-VLP that was detected in NALT and CLN. Such cells present in all the lymphoid tissues analyzed from non-immune mice have already been reported within murine splenic cells [11] and, recently, within human B cells from adults, infants and cord blood, and have been proposed to be responsible for an innate B cell response resulting from the interaction of 2/6-VLP with natural surface anti-VP6 Ab [19,20]. Thus, the high frequency of 2/6-VLP-specific B cells observed here may result from both innate and adaptive B cell responses.…”
Section: Igdmentioning
confidence: 78%
“…However, compared to results obtained with the same method, our results show that a4b7 expression by RV-specific B lymphocytes induced by i.n. administered nonreplicating Ag is lower than that observed in intestinal lymphoid tissues after oral administration of live virus in mice [15] (in this case up to 50% and 60% of RV-specific extrafollicular B cells expressed a4b7 in PP and MLN, respectively) or during an acute infection in children and adults [20,24]. This result suggests that a4b7 expression may probably not be a critical requirement for protection against RV infection after i.n.…”
Section: Igdmentioning
confidence: 80%
“…To develop new strategies for treating or preventing this disease, our laboratory is currently characterizing human virus-specific T and B cells in children and adults (16,23,24,48). We recently showed that healthy adults have very low frequencies of circulating CD4 ϩ and CD8…”
mentioning
confidence: 99%
“…B cells migrating through peripheral blood back to the gut should express the intestinal homing receptor ␣ 4 ␤ 7. Gonzales et al (6) found a mean percentage of 1.9 of memory B cells that bound RV DLP by flow cytometry analysis of peripheral blood cells obtained from healthy adults in Columbia, South America. In that study, the mean frequency of IgD Ϫ B cells that were both RV-specific and expressed ␣ 4 ␤ 7 was 3.3% in "large-" and 0.6% in "small-" sized memory B cells in acutely infected adults.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that adoptively transferred IgD Ϫ /␣ 4 ␤ 7 ϩ B cells, but not IgD ϩ /␣ 4 ␤ 7 ϩ or IgD Ϫ /␣ 4 ␤ 7 Ϫ B cells, cleared chronic RV infection in RAG-2-deficient mice that lack T and B cells (5). Recent studies determined that human RV-specific surface Ig ϩ B cells often express the ␣ 4 ␤ 7 molecule, as detected by a novel mAb specific for that heterodimer (6). We reasoned that analysis of the Ab repertoire in human RV-specific B cells should focus on these intestinal homing cells.…”
Section: H Uman Rotaviruses (Rv)mentioning
confidence: 99%